Milk Street instant pot : bold, fast, fresh--a revolution of flavor in an instant - Kimball, Christopher; Hirsch, J. M.; Locke, Michelle; Card, Matthew; Unger, Diane (Voracious, Little, Brown and Company, 2021)
Using fresh flavor combinations and innovative techniques from around the world, this cookbook shows home cooks how to make the most of their multicooker's unique capabilities with a vast array of one-pot recipes revealing how to prepare the same dish two ways.